La Restauración en las Filmotecas - Márquez Molleda, Berta; Moreno Hernández, Noelia; Revuelta Careaga, Carla; Sánchez Rodrigo, Laura (Cuadernos de Documentación Multimedia, 2018)
La Restauración en las Filmotecas